Angiotensin-(1-7) reduces norepinephrine release through a nitric oxide mechanism in rat hypothalamus - Gironacci, Mariela Mercedes (2000)
Angiotensin (Ang)-(1-7) elicits a facilitatory presynaptic effect on peripheral noradrenergic neurotransmission, and because biological responses to the heptapeptide on occasion are tissue specific, the present investigation was undertaken to study its action on noradrenergic neurotransmission at the central level. In rat hypothalamus labeled with [3H]-norepinephrine, 100 to 600 nmol/L Ang-(1-7) diminished norepinephrine released by 25 mmol/L KCl. This effect was blocked by the selective angiotensin type 2 receptor antagonist PD 123319 (1 μmol/L) and by the specific Ang-(1-7) receptor antagonist [D-Ala7]Ang-(1-7) (1 μmol/L) but not by losartan (10 nmol/L to μmol/L), a selective angiotensin type 1 receptor antagonist. The inhibitory effect on noradrenergic neurotransmission caused by Ang-(1-7) was prevented by 10 μmol/L N(ω)-nitro-L-arginine methylester, an inhibitor of nitric oxide synthase activity, and was restored by 100 μmol/L L-arginine, precursor of nitric oxide synthesis. Methylene blue (10 μmol/L), an inhibitor of guanylate cyclase considered as the target of nitric oxide action, as well as Hoe 140 (10 μmol/L), a bradykinin B2- receptor antagonist, prevented the inhibitory effect of the heptapeptide on neuronal norepinephrine release, whereas no modification was observed in the presence of 0.1 to 10μmol/L indomethacin, a cyclooxygenase inhibitor. Our results indicate that Ang-(1-7) has a tissue-specific neuromodulatory effect on noradrenergic neurotransmission, being inhibitory at the central nervous system by a nitric oxide-dependent mechanism that involves angiotensin type 2 receptors and local bradykinin production.